Implementation of Academic Supervision by School Principals to Improve Teachers’ Pedagogical Competence (A Narrative Qualitative Study at Primary Schools in the Border Area of East Kalimantan) - Hardian, Dafyar Eliadi; Ningsih, Nur; Amalia, Nita; Suyati, Suyati (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
This study employed a descriptive qualitative method with a narrative design, aiming to explore and understand the implementation of academic supervision by school principals in enhancing teachers’ pedagogical competence in primary schools located in the border region of East Kalimantan. The narrative approach was chosen to allow the researcher to reconstruct the personal and professional experiences of principals and teachers as meaningful narratives within the context of educational supervision. Data were collected through in-depth interviews, direct observation, and document analysis. The participants of this study included school principals, teachers, and school supervisors selected through purposive sampling, based on their direct involvement in academic supervision practices. Data analysis employed Miles and Huberman’s interactive model, which consists of data reduction, data display, and conclusion drawing/verification. Data validity was ensured through source and method triangulation, prolonged engagement in the field, and member checking to confirm the credibility of the findings with the participants. This methodological approach enabled the researcher to interpret the narratives of principals’ and teachers’ experiences in conducting academic supervision, highlight the strategies used to develop teachers’ pedagogical competencies, and uncover contextual challenges faced in remote and border-area schools.